UPAYA HUKUM KEBERATAN DALAM PENYELESAIAN SENGKETA PERDATA MELALUI GUGATAN SEDERHANA DI PENGADILAN NEGERI PONTIANAK - NIM. A1012191148, NORMAH (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACT In resolving cases, of course there is a judge as one of the law enforcers who has the task of being the decider in deciding the case. After the resolution of the Simple Claims case has been decided in the District Court of first instance, if one of the parties is not satisfied with receiving the decision, then one of the parties can submit legal action. So the main problem in this writing is